2023
DOI: 10.3390/ijms24010793
|View full text |Cite
|
Sign up to set email alerts
|

The Presence of Plasmids in Lactococcus lactis IL594 Determines Changes in the Host Phenotype and Expression of Chromosomal Genes

Abstract: The L. lactis IL594 strain contains seven plasmids (pIL1 to pIL7) and is the parental strain of the plasmid-free L. lactis IL1403, one of the most studied lactic acid bacteria (LAB) strain. The genetic sequences of pIL1 to pIL7 plasmids have been recently described, however the knowledge of global changes in host phenotype and transcriptome remains poor. In the present study, global phenotypic analyses were combined with transcriptomic studies to evaluate a potential influence of plasmidic genes on overall gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 29 publications
2
4
0
Order By: Relevance
“…Among them, the transcription of cadA, cbiO, pacL, and yuhE, encoding components of mono-and divalent cation efflux systems (Cs + , Co 2+ , Zn 2+ ), were most strongly activated. Interestingly, the phenotypic effect of enhanced tolerance to cesium, cadmium, and cobalt ions was observed in IL1619 and IL594, supporting our previous speculation of the important role of plasmid pIL5 in enhancing the cellular tolerance of L. lactis [11]. Here, we also confirmed the previously described phenomenon of plasmid-induced repression of all three components of the mtsABC operon encoding the manganese ABC transport system in L. lactis IL594 [10].…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…Among them, the transcription of cadA, cbiO, pacL, and yuhE, encoding components of mono-and divalent cation efflux systems (Cs + , Co 2+ , Zn 2+ ), were most strongly activated. Interestingly, the phenotypic effect of enhanced tolerance to cesium, cadmium, and cobalt ions was observed in IL1619 and IL594, supporting our previous speculation of the important role of plasmid pIL5 in enhancing the cellular tolerance of L. lactis [11]. Here, we also confirmed the previously described phenomenon of plasmid-induced repression of all three components of the mtsABC operon encoding the manganese ABC transport system in L. lactis IL594 [10].…”
Section: Discussionsupporting
confidence: 90%
“…Increased tolerance to antimicrobial compounds and metal ions represents an important mechanism of LAB environmental adaptation. Here, we showed that the presence of plasmids in L. lactis led to subtle differences in the tolerance of theirs hosts to several chemical compounds, with most changes observed in strain IL1619 with pIL5, confirming our previous suspicion of its importance in enhancing cell resistance in the multiplasmid L. lactis IL594 [ 11 ]. These findings imply that pIL5 may play a role in increasing cell defense by the action of its own resistance genes and/or by regulating the expression of the chromosomal ones.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations